Cellular ROS tolerance determines the effect of plumbagin on osteoclast differentiation - Sultanli, Sevinj; Schneider, Jakob; Burkart, Sandy; Binder, Marco; Hieke-Kubatzky, Katharina (The FASEB journal, 2023)
Plumbagin is used in traditional medicine because of its anti-inflammatory and anti-microbial properties. As a naphthoquinone, plumbagin triggers the production of reactive oxygen species (ROS). In vitro cancer studies showed that plumbagin triggers apoptosis in cancer cells through ROS production. As cancer-mediated chronic inflammation can affect bone density, it was hypothesized that plumbagin might directly inhibit the formation of bone-resorbing osteoclasts. We previously showed that the effect of plumbagin on osteoclastogenesis differed between bone marrow-derived macrophages and the macrophage cell line RAW 264.7. Although RAW 264.7 macrophages are able to initiate the gene program required for osteoclastogenesis, only primary macrophages successfully differentiate into osteoclasts. Here, we show that RAW 264.7 cells are more sensitive toward plumbagin-induced apoptosis. In the presence of plumbagin and the cytokine RANKL, which triggers ROS production to drive osteoclastogenesis, RAW 264.7 macrophages produce increased amounts of ROS and die. Addition of the ROS scavenger N-acetyl cysteine prevented cell death, linking the failure to differentiate to increased ROS levels. RAW 264.7 cells show reduced expression of genes protective against oxidative stress, while primary macrophages have a higher tolerance toward ROS. Our data suggest that it is indispensable to consider cell (line)-intrinsic properties when studying phytochemicals.